2019
DOI: 10.15823/p.2019.136.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collegial School Management on Improvement of Students’ skills

Abstract: The study aims to investigate the effect of collegial school management on the prevention of disruptive behaviors and students’ life skills. A quasi-experimental research design, a structured questionnaire, and the cluster random samples were used in the study. It is found that school management increase the prevention of disruptive behaviors and students’ life skills, and collegial school management predicts the prevention of disruptive behaviors and students’ life skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…The Beta Standardized coefficient, .927 for the experimental group, and .794 for the control group of artistic works demonstration explain, respectively, 92.7% and 79.4% of the variance in the total score of artistic skills development predicted by artistic works demonstration. The result is in coherence with prior published research (Montgomery, 2017;Baldus & Wilson, 2016;Maureen, 2019;De La Cruz, 2017;Xhomara, 2019;Lekue, 2015;Ma, 2021;Yokochi & Okada, 2021;Lazutina et al, 2016;Ruotsalainen, 2017;De Backer et al, 2012;Zourntos, 2013;Necka & Hlawacz, 2013;Jaracz & Borkowska, 2020), who argued that artistic works demonstration predicts artistic skills development. As a final result, hypothesis # 2: Artistic works demonstration predicts artistic skills development of arts master students, is supported.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The Beta Standardized coefficient, .927 for the experimental group, and .794 for the control group of artistic works demonstration explain, respectively, 92.7% and 79.4% of the variance in the total score of artistic skills development predicted by artistic works demonstration. The result is in coherence with prior published research (Montgomery, 2017;Baldus & Wilson, 2016;Maureen, 2019;De La Cruz, 2017;Xhomara, 2019;Lekue, 2015;Ma, 2021;Yokochi & Okada, 2021;Lazutina et al, 2016;Ruotsalainen, 2017;De Backer et al, 2012;Zourntos, 2013;Necka & Hlawacz, 2013;Jaracz & Borkowska, 2020), who argued that artistic works demonstration predicts artistic skills development. As a final result, hypothesis # 2: Artistic works demonstration predicts artistic skills development of arts master students, is supported.…”
Section: Discussionsupporting
confidence: 89%
“…A lot of research is carried out to investigate the relationship between artistic works demonstration and different variables, including the artistic skills development of art students at university. Jaracz and Borkowska (2020), as well as Montgomery (2017), indicated that artistic works demonstration, such as dancing, painting or signing are connected significantly to artistic skills development; meanwhile, Xhomara (2019) found out that artistic collegial principalship impacts the artistic knowledge and competencies development. Other research study including different forms of artistic demonstration, such as dancing, signing, and sculpting works that are related significantly with development and improvement of artistic skills.…”
Section: Relationship Between Artistic Work Demonstration and Artisti...mentioning
confidence: 94%
See 1 more Smart Citation
“…Also, Okereke (2016) indicated that the collaborative approach was strongly associated with decreased problem behaviour among students. Further, Löfgren and Karlsson (2016) and Xhomara (2019) reported that collegiality in schools reduced conflicts and led to consensus, which impacted teachers' professional work and contribution to school development, enhancing students' discipline and preventing disruptive behaviours. With the findings of the study consistent with the findings of all previous, it can be inferred that collaborative leadership practices are related to students' discipline.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analytic review, Okereke (2016) revealed that a collaborative approach was strongly associated with decreased problem behaviour among students. Further, Xhomara (2019) in a study involving headteachers, teachers, and students in schools in Albania found out that collegial school management increased the prevention of disruptive behaviours. However, the context of the studies was outside the African context hence differences in school environments.…”
Section: Collaborative Culture Practices and Students Disciplinementioning
confidence: 99%